2006
DOI: 10.1016/j.febslet.2006.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of pro‐apoptotic protein HGTD‐P with heat shock protein 90 is required for induction of mitochondrial apoptotic cascades

Abstract: HGTD-P is a hypoxia-responsive pro-apoptotic protein that transmits hypoxic signals directly to mitochondria. When overexpressed, HGTD-P induces cell death via typical mitochondrial apoptotic cascades. However, much is unknown about post-transcriptional modification and signaling networks of HGTD-P in association with cell death-regulating proteins. We performed yeast two-hybrid screening to identify the molecules involved in HGTD-P-mediated cell death pathways. In this study, we show that heat shock protein 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
(30 reference statements)
1
11
0
Order By: Relevance
“…HSP90 was found to be a negative regulator of the mitochondrial cytochrome c-dependent apoptosis pathway (66). The association of HSP90 to Bcl-2 is required to prevent mitochondrial apoptotic cascades (67), whereas in another type of cell, HSP90 was found to interact with proapoptotic proteins inducing mitochondrial apoptotic cascades (68). The involvement of HSP90 in PCD is consistent with our proposed role for HSP83 involvement in drug-induced PCD in Leishmania.…”
Section: Discussionsupporting
confidence: 76%
“…HSP90 was found to be a negative regulator of the mitochondrial cytochrome c-dependent apoptosis pathway (66). The association of HSP90 to Bcl-2 is required to prevent mitochondrial apoptotic cascades (67), whereas in another type of cell, HSP90 was found to interact with proapoptotic proteins inducing mitochondrial apoptotic cascades (68). The involvement of HSP90 in PCD is consistent with our proposed role for HSP83 involvement in drug-induced PCD in Leishmania.…”
Section: Discussionsupporting
confidence: 76%
“…Although increasing evidence shows that HSPs and GRPs can provide a protective effect against cell death in some situations [12,15,16,22,23], various HSPs have been found to accelerate the apoptotic processes. For example, HSP90b has been involved in the induction of NO synthesis and apoptosis, both of which are involved in OA pathogenesis [24]. In this study, we have showed that IL-1b (a stimulus with capacity to induce NO synthesis and apoptosis in chondrocytes) [25,26] was able to induce gene expression and protein synthesis of HSP90b as well as GRP78.…”
Section: Discussionmentioning
confidence: 69%
“…The expression of several hypoxia-induced, proapoptotic proteins is increased in tumor tissues. For example, BNip3 protein is a proapoptotic mitochondrial protein that binds hsp90 and activates caspase cascades, leading to apoptotic cell death [10]. In contrast, many types of human cancers showed increased expression of BNip3 protein, which is up-regulated in hypoxic conditions [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%